Neurogenetics of confinement-induced behavioral alterations. - Heredia, Fabiana (2023)
The molecular and neural mechanisms underlying the translation of physical confinement to internal state changes and how these alter behavior are poorly understood and very difficult to study in natural settings due to an excessive number of possible confounding factors. Innate behaviors, which are complex, genetically-encoded behaviors that proceed with a predictable sequence, provide a unique window to study the effects of confinement on behavior. Adding this to the power of a genetically tractable model organism, we aim to help unravel both the molecular and cellular foundations of behaviorally-relevant, confinement-induced changes in internal states. Here, we start to genetically dissect the wing expansion behavior that Drosophila flies perform upon eclosing from their puparium. The execution of this behavior, which is triggered by the hormone Bursicon, is strongly negatively-regulated by spatial confinement. Namely, wing expansion behavior occurs within 30 min when animals eclose in normal, unconfined conditions, yet it is delayed to > 180 min upon eclosion into a confined environment. The molecular mechanisms controlling this wing expansion decision process upon confinement are poorly understood. By chance, we found a background mutation segregating in Drosophila stocks where wing expansion behavior is severely compromised specifically under confinement, not under normal unconfined conditions. We are mapping this mutation in the hope that it provides a unique entrance into the molecular and neural underpinnings of confinement-induced behavioral control. In parallel, we have performed two studies to identify factors that are affected in the central nervous system of animals undergoing spatial confinement: a genome wide time-series transcriptomic study of confined and unconfined animals and a small-scale genetic screen for neuropeptides and receptors affecting this confinement-induced behavioral response. We will present the preliminary analyses of these studies. We hope that these approaches will help clarify how spatial confinement alters wing expansion behavior, and provide further insight on how environmental changes affect behavior and health